‘For Me, In My Present State’: Kant on Judgments of Perception and Mere Subjective Validity - Janum Sethi (Journal of Modern Philosophy)
Few of Kant’s distinctions have generated as much puzzlement and criticism as the one he draws in the Prolegomena between judgments of experience, which he describes as objectively and universally valid, and judgments of perception, which he says are merely subjectively valid. Yet the distinction between objective and subjective validity is central to Kant’s account of experience and plays a key role in his Transcendental Deduction of the categories. In this paper, I reject a standard interpretation of the distinction, according to which judgments of perception are merely subjectively valid because they are made without sufficient investigation. In its place, I argue that for Kant, judgments of perception are merely subjectively valid because they merely report sequences of perceptions had by a subject without claiming that what is represented by the perceptions is connected in the objects the perceptions are of. Whereas the interpretation I criticize undercuts Kant’s strategy in the Deduction, I argue, my interpretation illuminates it.